A Geometria esférica e os sólidos platônicos - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
This thesis presents a new demonstration of the result FOR Plato not the fourth century BC in Ancient Greece, to que There hum Finite number of classes Poliedro Regular congruent, using a basic theory of spherical geometry, of the agreement with the work " The solid platonicos " make Dr. John Lucas Marques Barbosa University of Ceará, presented in Manaus.
Keywords: Poliedros regulares congruentes; Sólidos platônicos; Spherical geometry; Platonic solids; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA